ChemInform Abstract: Direct Nucleophilic Addition to N‐Alkoxyamides. Issue 26 (6th June 2013) - Yanagita, Yuta; Nakamura, Hugh; Shirokane, Kenji; Kurosaki, Yusuke; Sato, Takaaki; Chida, Noritaka
Abstract The nucleophilic addition to N‐alkoxyamines to access multisubstituted amines is described.